Employer Brand Knowledge (EBK), Sustainability Practices and Employer Attractiveness: A Perspective of Millennial Employees - Roslan, Farizah; Samat, Nusrah; Hussein, Norashikin (Information Management and Business Review, 2024)
Employer attractiveness is crucial in talent management as it helps attract, retain, and engage top talent, thereby ensuring a competitive edge and long-term organizational success. This study aims to determine the relationship between Employer Brand Knowledge (EBK) and various dimensions of sustainability practices on employer attractiveness, particularly among Millennial employees. A quantitative research method was employed, with 90 questionnaires collected from Millennial employees in a publicly listed company in Malaysia. The data was analyzed using SPSS version 25.0 to test the hypotheses. The findings reveal that only one dimension of EBK namely employer image has a significant positive relationship with employer attractiveness. Contrary to our expectations, none of the sustainability practices was found to be related to employer attractiveness. This study contributes to a deeper understanding of how EBK influences the perception of employer attractiveness as it not only broadens the theoretical understanding but also provides practical insights for employers seeking to improve their attractiveness to the Millennial workforce. It is also suggested that employers who are more familiar with employees, have a positive reputation, and maintain a strong image are more likely to be attractive to millennials. Implications and recommendations for future research are also discussed in the study.